7th Scientific and Professional Conference on Judo - "Applicable Research in Judo", 20-21. June 2024, Porec, Croatia - Proceedings Book - Sertic, H.; Corak, S.; Segedi, I. (7th Scientific and Professional Conference on Judo - "Applicable Research in Judo", 20-21. June 2024, Porec, Croatia - Proceedings Book, 2024)
Ladies and gentleman, dear JUDOKAS, all participants and readers of the 7th SCIENTIFIC AND PROFESSIONAL CONFERENCE "APPLICABLE RESEARCH IN JUDO" proceedings book.